No more pencils, no more books, no more teacher's dirty looks! - De Groat, Diane (HarperCollins, 2006)
Gilbert and his first-grade classmates are nervous about their performance on the last day of school, curious about the awards they will receive, sad to be leaving their teacher, and excited about summer vacation.